Hierarchical structures based on gold nanoparticles embedded into hollow ceria spheres and mesoporous silica layers with high catalytic activity and stability. (1st October 2015) - Zhang, Yiwei; Xu, Yuanmei; Zhou, Yuming; Xiang, Sanming; Sheng, Xiaoli; Wang, Qianli; Zhang, Chao
Abstract : CeO2 /Au@mSiO2 composite multifunctional materials were synthesized, and this hollow hierarchical catalyst exhibited superior catalytic activity and stability. Abstract : A uniform hollow CeO2 /Au@mSiO2 core–shell catalyst with a hierarchical structure was fabricated successfully. The preparation method involves the synthesis of high surface area and porous hollow CeO2 nanospheres, a sequential deposition of sub-10 nm Au nanoparticles to obtain CeO2 /Au, coating the particles with mesoporous SiO2 shells through a sol–gel process and a calcination process at a desired temperature to obtain a mesoporous silica shell. The final obtained product was characterized by several techniques, including transmission electron microscopy (TEM), UV-Vis spectroscopy, X-ray diffraction (XRD) and energy dispersion X-ray spectroscopy (EDS). It is found that CeO2 /Au@mSiO2 composite multifunctional materials have a multilayer structure and gold nanoparticles can be embedded into the hollow ceria sphere and the mesoporous silica layer. Compared with the solid CeO2 /Au@mSiO2 catalyst, the hierarchical structures of the hollow CeO2 /Au@mSiO2 possess open unique hierarchical pores to expose the catalytically active component, including the hollow central structure and mesopores from the CeO2 layer and the silica shell. The results of the reduction of 4-nitrophenol (4-NP) indicate that the synthesized hollow hierarchical catalysts exhibit superior catalytic performance to the traditional core–shell structure and can be easily recycled without a decrease of the catalytic activities in the reaction.